Membrane Water Treatment: A Review in Islamic and Science Perspective - Ainaa Mardhiah Wan Zahari, Wan; Mohd Subri, Irwan; Ab Rahman, Azman; Hafez Mohd Isa, Mohd; SanusiAzmie, Ahmad; Abdul Mutalib, Mahazan; Adib Mohamad Salih, Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
This paper is about a review of membrane water treatment according to Islamic and scientific perspectives. Nowadays, water, as the most precious human right, is facing many issues regarding its misuse, leading to critical water shortages and contamination. Various methods have been introduced to tackle this water issue. One of the aspects is having water treatment or water recycling using the process of membrane water treatment. So, the aim of this paper is to explore the concept of water and how the treatment and purification of water in Islam and science views. Next, this paper also suggested the membrane water treatment as the method and process to treat and purify the water, whether this water membrane process is complying with Shariah compliance or vice versa. The methodology of this paper is a qualitative approach by using document analysis of article papers, fiqhturath books, and also related document references. The result reveals the water treated by the membrane water treatment process is pure (tahir) according to Islam and science perspectives.